The Effect of Binaural Audio Technology on Audience Immersion in Horror Films - Febri, I Wayan Nain (Journal of Dialogos, 2025)
This research aims to explore the influence of binaural audio technology on the audience's level of immersion in horror films. The background to this research is based on the development of increasingly sophisticated audio technology and its potential to improve the film watching experience. The aim of this research is to measure how much influence binaural audio technology has on the audience's perception and emotional response when watching horror films. The research method used was an experimental design with a population consisting of students majoring in Film and Media at a university in Indonesia. Samples were taken randomly from as many as 60 people who were divided into two groups: a control group who watched films with regular stereo audio and an experimental group who watched films with binaural audio. Data collection techniques were carried out through questionnaires filled out by participants after watching the film, as well as physiological measurements such as heart rate and galvanic skin response to assess the level of tension and emotional involvement. Data analysis was carried out using statistical tests to compare differences between the two groups. The results showed that the group watching with binaural audio experienced a higher level of immersion compared to the control group, indicated by higher questionnaire scores and more intense physiological responses. In conclusion, binaural audio technology significantly increases audience immersion in horror films, which could have a positive impact on the film industry in creating more immersive and engaging viewing experiences.